Kejahatan Perdagangan Orang dalam Hukum Positif di Indonesia - Pinem, Serimin (Jurnal Ilmiah Penegakan Hukum, 2023)
The crime of human trafficking is a very complex crime that is difficult to eradicate. The crime of human trafficking usually affects not only one area of life, but also many other areas of life. The crime of human trafficking is also a crime that violates other human rights. Human trafficking is a terrible crime and one of the fastest growing crimes in the world. especially women as a vulnerable group. The problem that will be discussed in this paper is the causes of crime in society, this broadly includes defining the condition of the physical environment, as well as the need to study the relationship between human trafficking for people who are trapped in poverty, because they do not have different opportunities to realize: 1. economic rights, 2. education, 3. health and information. The crime of human trafficking is not only in urban areas, but also in rural areas, and the victims are women and children, as well as a lack of knowledge and low levels of education which is a potential benefit for individuals who are looking for victims of the crime of human trafficking